Methotrexate Decreases Tenofovir Exposure in Antiretroviral-Suppressed Individuals Living With HIV. (15th December 2020) - Gingrich, David; Deitchman, Amelia N.; Kantor, Amy; Huang, Liusheng; Stein, James H.; Currier, Judith S.; Hsue, Priscilla Y.; Ribaudo, Heather J.; Aweeka, Francesca T.
Abstract : Background: To mitigate increased risk of premature cardiovascular disease in antiretroviral therapy (ART) suppressed adults living with HIV (PWH), low-dose methotrexate (LDMTX) was evaluated in a multicenter randomized placebo controlled clinical trial of 176 PWH taking various ART regimens (ACTG A5314). Given shared methotrexate (MTX) and tenofovir (TFV) pharmacokinetic (PK) pathways, a substudy was conducted to investigate whether LDMTX alters TFV exposure. Methods: Adults virally suppressed on ART for >24 weeks were randomized to LDMTX or placebo. The first 66 participants taking a tenofovir disoproxil fumarate-containing regimen underwent intensive PK sampling over 24 hours after the second dose of LDMTX 10 mg or placebo. TFV and MTX levels were quantified using validated mass spectrometry methods. TFV PK between LDMTX and placebo groups were compared and MTX PK was characterized. Results: Forty-eight participants completed this substudy (n = 20 on LDMTX and 28 on placebo). Baseline characteristics were balanced except for protease inhibitor (PI)-use (25% in LDMTX and 43% in placebo groups). For TFV, AUC6 (primary endpoint), and AUC24, imputed, Cmax, and Cmin (secondary endpoints) were on average 22%, and 24%, 27%, and 31% less in the LDMTX versus placebo groups, with reductions in secondary endpoints reaching statistical significance. Additional analyses suggested a greater reduction in the absence of PI although not significant. Conclusion: Lower TFV AUC24, imputed and Cmax indicates that LDMTX reduces TFV exposure in PWH. However, this change was modest, not warranting a change in TFV dosing at this time. Further studies of TFV PK with LDMTX, especially without PI co-administration, are warranted. Abstract : Supplemental Digital Content is Available in the Text.